EUS-directed transgastric endoscopic retrograde cholangiopancreatography versus laparoscopic-assisted ERCP versus deep enteroscopy-assisted ERCP for patients with RYGB - Kochhar, Gursimran S.; Mohy-ud-din, Nabeeha; Grover, Abhinav; Carleton, Neil; Kulkarni, Abhijit; Farah, Katie; Dhawan, Manish; Thakkar, Shyam (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound-directed transgastric endoscopic retrograde cholangiopancreatography (ERCP) (EDGE) is a novel technique for managing pancreaticobiliary diseases in patients with a history of Roux-en-Y Gastric Bypass (RYGB). It has shown to have high technical success rates and fewer adverse events as compared to laparoscopic-assisted ERCP (LA-ERCP). We compared the technical success and clinical outcomes of EDGE vs. LA-ERCP vs. E-ERCP.Patients and methods A retrospective chart review was performed for 56 patients, of whom 18 underwent LA-ERCP, 12 underwent E-ERCP, and 26 had EDGE, and a comparison of technical success and complication rates was done.Results Baseline demographic characteristics of patients undergoing these procedures, including age and gender, were comparable. The technical success rate for patients in the EDGE group were 100 % (n = 26), compared with 94 % (n = 17) and 75 % (n = 9) in the LA-ERCP and E-ERCP groups (P = 0.02). In the EDGE group, 8 % of patients (n = 2) had bleeding, and 4 % of patients (n = 1) had lumen-apposing metal stent migration occur during the procedure. In the LA-ERCP group 6 % (n = 1) of patient had bleeding, 6 % (n = 1) post-ERCP pancreatitis and 6 % (n = 1) were diagnosed with an intra-abdominal infection post-procedure. Time to complete the EDGE procedure was significantly shorter at 79 ± 31 mins, compared with 158 ± 50 mins for LA-ERCP and 102 ± 43 mins for E-ERCP (P < 0.001).Conclusion EDGE is a novel procedure with short procedure times and an effective alternative to LA-ERCP and E-ERCP in management of pancreaticobiliary diseases in patients with a history of RYGB.